Substitutie of combinatie
- \(\left\{\begin{matrix}3x-3y=\frac{549}{70}\\-2x=-y+\frac{-134}{35}\end{matrix}\right.\)
- \(\left\{\begin{matrix}-4x-6y=\frac{41}{4}\\3x-y=\frac{-45}{8}\end{matrix}\right.\)
- \(\left\{\begin{matrix}2y=\frac{-13}{342}-x\\-4x-4y=\frac{-82}{171}\end{matrix}\right.\)
- \(\left\{\begin{matrix}3x-y=10\\-4x=4y+\frac{152}{3}\end{matrix}\right.\)
- \(\left\{\begin{matrix}4x+3y=\frac{-818}{255}\\4x+y=\frac{-998}{255}\end{matrix}\right.\)
- \(\left\{\begin{matrix}-5y=\frac{-795}{38}-3x\\x+y=\frac{191}{38}\end{matrix}\right.\)
- \(\left\{\begin{matrix}-2y=\frac{883}{182}-5x\\3x+y=\frac{345}{182}\end{matrix}\right.\)
- \(\left\{\begin{matrix}6x+2y=\frac{-656}{209}\\-x+3y=\frac{-1094}{209}\end{matrix}\right.\)
- \(\left\{\begin{matrix}3x-2y=\frac{-1}{9}\\-3x-y=\frac{-5}{9}\end{matrix}\right.\)
- \(\left\{\begin{matrix}4y=\frac{-805}{136}-3x\\-x-y=\frac{231}{136}\end{matrix}\right.\)
- \(\left\{\begin{matrix}-5x-4y=-59\\x=y+10\end{matrix}\right.\)
- \(\left\{\begin{matrix}-6y=\frac{841}{68}+x\\-6x-4y=\frac{483}{34}\end{matrix}\right.\)
Substitutie of combinatie
Verbetersleutel
- \(\left\{\begin{matrix}3x-3y=\frac{549}{70}\\-2x=-y+\frac{-134}{35}\end{matrix}\right.\qquad V=\{(\frac{17}{14},\frac{-7}{5})\}\)
- \(\left\{\begin{matrix}-4x-6y=\frac{41}{4}\\3x-y=\frac{-45}{8}\end{matrix}\right.\qquad V=\{(-2,\frac{-3}{8})\}\)
- \(\left\{\begin{matrix}2y=\frac{-13}{342}-x\\-4x-4y=\frac{-82}{171}\end{matrix}\right.\qquad V=\{(\frac{5}{18},\frac{-3}{19})\}\)
- \(\left\{\begin{matrix}3x-y=10\\-4x=4y+\frac{152}{3}\end{matrix}\right.\qquad V=\{(\frac{-2}{3},-12)\}\)
- \(\left\{\begin{matrix}4x+3y=\frac{-818}{255}\\4x+y=\frac{-998}{255}\end{matrix}\right.\qquad V=\{(\frac{-16}{15},\frac{6}{17})\}\)
- \(\left\{\begin{matrix}-5y=\frac{-795}{38}-3x\\x+y=\frac{191}{38}\end{matrix}\right.\qquad V=\{(\frac{10}{19},\frac{9}{2})\}\)
- \(\left\{\begin{matrix}-2y=\frac{883}{182}-5x\\3x+y=\frac{345}{182}\end{matrix}\right.\qquad V=\{(\frac{11}{14},\frac{-6}{13})\}\)
- \(\left\{\begin{matrix}6x+2y=\frac{-656}{209}\\-x+3y=\frac{-1094}{209}\end{matrix}\right.\qquad V=\{(\frac{1}{19},\frac{-19}{11})\}\)
- \(\left\{\begin{matrix}3x-2y=\frac{-1}{9}\\-3x-y=\frac{-5}{9}\end{matrix}\right.\qquad V=\{(\frac{1}{9},\frac{2}{9})\}\)
- \(\left\{\begin{matrix}4y=\frac{-805}{136}-3x\\-x-y=\frac{231}{136}\end{matrix}\right.\qquad V=\{(\frac{-7}{8},\frac{-14}{17})\}\)
- \(\left\{\begin{matrix}-5x-4y=-59\\x=y+10\end{matrix}\right.\qquad V=\{(11,1)\}\)
- \(\left\{\begin{matrix}-6y=\frac{841}{68}+x\\-6x-4y=\frac{483}{34}\end{matrix}\right.\qquad V=\{(\frac{-19}{17},\frac{-15}{8})\}\)